MEMURNIKAN KEWENANGAN MAHKAMAH KONSTITUSI SEBAGAI LEMBAGA PENGAWAL KONSTITUSI (THE GUARDIAN OF THE CONSTITUTION) - Sudirman Sudirman (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2016)
Stated in constitution (UUD NRI Tahun 1945), one of Constitutional Court authority is guarding the constitution, that means reviewing any law against the constitution. Whereas review any ordinances and regulation made under law would fall into the authority of Supreme Court. Based on stufen theory, ordinances and regulation made under law is inseparable and is the continuation of the constitution, so that authority review must fall under Constitutional Court as the guardian of the constitution. But constitution regulations see ordinances and regulation made under any law should be separated from constitution, so review authority fall under Supreme Court. This condition provokes dualism judicial review, addressing problems that able to disturb the goverment system of Indonesia. This article elaborates dualism judicial review problem and idea of purifying constitutional court authority as the guardian of constitution. http://dx.doi.org/10.17977/um019v1i12016p048